Analysis the Flood Resulting from supposed collapse Using HEC-RAS Program - خلود معلا,; عزالدين حسن , (Latakia University Journal -Engineering Sciences Series, 2023)
Dams, since their inception, have provided tremendous services to humanity, but at the same time they expose millions to danger in the event of their collapse. When the dam collapses, large amounts of water are released threatening the lives and property of people, and this is due to the short time available for warning and evacuation. This research aims at analyzing the flood wave resulting from a supposed collapse of the proposed dam on the Marakia River and predicting the parameters of the breach formed, the maximum flow out of it as well as the time required for the development of the breach, and then developing the resulting inundation maps to know the affected areas, and thus providing the scientific basis that can be relied upon when Develop evacuation and emergency plans, and draw up urban policies. The research methodology relied on the application of Zahank's equations to predict the parameters of the breach and the maximum peak flow and the use of the programs Arc GIS, Hec-Ras to build a dam collapse model according to a scenario that is the flow of water from above the top of the dam, which resulted in a flood wave with a maximum intensity of 42686.8 m3 / s and the exit of a quantity 110 MCM of water from the lake through the breach formed, and in this scenario the breach develops very quickly reaching its final shape which negatively affects the time available for warning and the short period for evacuation.